Cooperative behavior in pre-state societies: an agent based approach to the Axum civilization - Vasellini, Riccardo; Ferrandino, Gilda; Sernicola, Luisa; Vilone, Daniele; Mocenni, Chiara (Frontiers in Complex Systems, 2025)
IntroductionThis study intends to test the hypothesis that, contrary to traditional interpretation, the social structure of the polity of Aksum–especially in its early stages–was not characterized by a vertical hierarchy with highly centralized administrative power, and that the leaders mentioned in the few available inscriptions were predominantly ritual leaders with religious rather than coercive political authority. This hypothesis, suggested by the available archaeological evidence, is grounded in Charles Stanish's model, which posits that pre-state societies could achieve cooperative behavior without the presence of coercive authority.MethodsUsing agent-based modeling applied to data inspired by the Aksum civilization, we examine the dynamics of cooperation in the presence and absence of a Public Goods Game.ResultsResults show that while cooperative behavior can emerge in the short term without coercive power, it may not be sustainable over the long term, suggesting a need for centralized authority to foster stable, complex societies.DiscussionThese findings provide insights into the evolutionary pathways that lead to state formation and complex social structures.